Pendidikan Akhlak di Pendidikan Dasar MI/SD - Muhammad Ikrar Maulana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This Moral education in basic education has an important role in shaping the character and morals of children from an early age. This research aims to highlight the importance of moral education in the basic education curriculum. This research method includes analysis of literature and secondary data related to the effectiveness of moral education in early childhood. The research results show that the integration of moral education in the basic education curriculum can increase moral awareness, empathy and positive behavior in students. The implications of this research indicate the need for greater emphasis on moral education at the basic education level to form a generation with noble morals.